2013
DOI: 10.3390/cancers5030901
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Dual CDC7/CDK9 Inhibitor in Multiple Myeloma Cellular Models

Abstract: Two key features of myeloma cells are the deregulation of the cell cycle and the dependency on the expression of the BCL2 family of anti-apoptotic proteins. The cell division cycle 7 (CDC7) is an essential S-phase kinase and emerging CDC7 inhibitors are effective in a variety of preclinical cancer models. These compounds also inhibit CDK9 which is relevant for MCL-1 expression. The activity and mechanism of action of the dual CDC7/CDK9 inhibitor PHA-767491 was assessed in a panel of multiple myeloma cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Hence PHA-767491 is a dual DDK/Cdk9 inhibitor. Recent studies have suggested that inhibition of Cdk9, a kinase that targets RNA Polymerase II, might enhance the apoptotic response induced by PHA-767491 in some cell lines [43] [45] . Modifications of this compound led to the identification of several other potent inhibitors of DDK with some exhibiting superior selectivity and sensitivity [46] [48] .…”
Section: Introductionmentioning
confidence: 99%
“…Hence PHA-767491 is a dual DDK/Cdk9 inhibitor. Recent studies have suggested that inhibition of Cdk9, a kinase that targets RNA Polymerase II, might enhance the apoptotic response induced by PHA-767491 in some cell lines [43] [45] . Modifications of this compound led to the identification of several other potent inhibitors of DDK with some exhibiting superior selectivity and sensitivity [46] [48] .…”
Section: Introductionmentioning
confidence: 99%
“…Major pharmaceutical companies such as Bayer (BAY1143572/ Atuveciclib), Pfizer (PHA-767491), Eli Lilly (LY2857785), and AstraZeneca (AZ5576) have developed their own CDK9 inhibitors which are being tested in pre-clinical and clinical studies of many disease models including B-or T-Cell Leukemia/Lymphoma, esophageal adenocarcinoma, acute myelogenous leukemia, primary peritoneal carcinoma, chronic lymphocytic leukemia, relapsed multiple myeloma, non-Hodgkin's lymphoma, acute lymphoblastic leukemia, acute biphenotypic leukemias, advanced breast cancer, non-small cell lung cancer, solid advanced tumors, etc. [244][245][246][247][248][249]. Including Alvocidib, there are several CDK9 inhibitors including Dinaciclib, Seliciclib, Atuveciclib, Voruciclib, and SNS-032, which are being examined in clinical trials for treatments of these diseases [250][251][252][253] (Table 3).…”
Section: Suppressing P-tefb Activitymentioning
confidence: 99%
“…However, only two reports have appeared in the literature concerning CDC7 inhibition in myeloma cells. In one, PHA-767491, an inhibitor of both CDC7 and CDK9, demonstrated anti-myeloma activity both in cells obtained from patients and in cell cultures [ 152 ]. Another compound, the related pyrrolopyridinone (designated 89S), inhibited two myeloma cell lines at low micromolar concentrations [ 153 ].…”
Section: Cell Cycle Control S/tkmentioning
confidence: 99%